O ensino de escovação e promoção da saúde bucal em crianças pré-escolares com autismo - Marega, Tatiane (Universidade Federal de São Carlos, 2008)
Studies have shown that autistic adults and adolescents have a high incidence of cavities due to their substandard practices of oral hygiene. Disruptive behaviors like flinching or fleeing are commonly observed during toothbrushing, as well as agonistic conduct during dental treatment. Few studies have addressed the improvement of toothbrushing efficacy as a form of preventing these problems, and most of the existing works are poor in methodology. This study evaluates the effectiveness of a toothbrushing training program upon children of five to six years of age who have been medically diagnosed as autistic. The children were randomly divided into groups G1, G2 and G3. G1 had training on the use of conventional toothbrushes, with an accompanying song and physical guidance; G2 had electric toothbrush training and physical assistance; group G3 had electric toothbrush training, associated to a song and physical assistance. Video recordings of the training sessions were used to determine the brushing steps assimilated by the children, as well as their autonomy and ability to complete each of the steps along the study. Hygiene results were evaluated through a sequence of treatments and probes. The use of electric toothbrushes apparently resulted in better removal of plaque, even under adverse conditions. G3 showed better plaque indexes than the other two groups, and G2 had better results than G1, suggesting that the use of electric toothbrushes associated to a song and physical assistance can optimize oral hygiene in autistic children. Overall, five-year-olds had better results than sixyear- olds, suggesting that younger children have a lower incidence of adverse behavior (e.g. nausea or vomiting) during toothbrushing.
Keywords: Autismo; Música; Odontologia; Educação especial; Saúde bucal; Autism; Electric toothbrush; Music; Odontology; Special education; Toothbrushing; Behavior; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL